TECHNOLOGY, ANALYSIS, AND STUDY DEVELOPMENT OF HEPATOPROTEC-TIVE ACTION OF SUPPOSITORIES WITH RIBOXINUM - O. V. Michnik; L. A. Michnik; I. V. Skulte; E. O. Sergeeva; S. G. Tiraspolskaya (Фармация и фармакология (Пятигорск), 2015)
То elaborate the composition of the suppositories with riboxiniirn we have studied physical and chemical, and structural and mechanical characteristics of different bases. Witepsol-H15 was chosen as a preferable base. We have carried out the quality estimation of the developed suppositories in accordance with regulatory documentation. The analysis methods offered are validated and proved to be specific, right and precise. The relative error of analysis is equal to ±0.98%. Supposito-ries with riboxinum at dose 15 mg/kg shows signified hepatoprotective action at white rats with experimental acute toxic hepatitis evoked by carbon tetrachloride injection, which ex-ceeds the similar pills effect